Effects of Kangaroo Mother Care on Physiological Parameters of Low-Birth-Weight Neonates - Amna Mateen, Nagham Nawaz Awan, Syeda Shireen Gul, Bushra Adeel, Sana Razzak, Saira Mushtaq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Maternal skin contact has impact on physiological parameters in newborns, some studies showed positive effects but as we live in under developing country and the data on impact of kangaroo mother care (KMC) on physiological parameters is very limited. We hypothesized that KMC is effective in stabilizing the heart rate, respiratory rate and maintaining the oxygen saturation and body temperature of low birth weight (LBW) newborns. Objective: The aim of the study was to determine effects of 3 hours KMC on physiological parameters such as body temperature, heart rate, respiratory rate and oxygen saturation in LBW neonates. Study Design: Observational Quasi-experimental study Study Setting: This study was conducted in Department of Neonatology, Children Hospital, PIMS, Islamabad, Pakistan from 1st June 2022 to 1st December 2022. Methodology: The neonates were hemodynamically stable admitted in NICU and Nursery of Children Hospital, PIMS with LBW with the bodyweight <2 kg was enrolled in the study after taking the consents from mother or other female attendant. Data were collected by structured questionnaire and observational checklist after taking consent from each participant. After inclusion neonates was received KMC for 03 hours. Participants physiological parameters were monitored closely before and after KMC. The statistical analysis was done by using SPSS version 20. Results: Out of the 60 mother-child couples enrolled in the study. There was high frequency of neonates between 1-1.5 kgs with 36.7%. Out of 60, 33 were baby boys and 27 were baby girls. After three hours of KMC, temperatures showed significant increased (p<0.001). Most infants’ temperatures were maintained during KMC, and no cases of hypothermia were reported. Also, statistically significant increases in heart rate were seen throughout KMC (p<0.001), with mean increases of exhibited bradycardia before starting KMC, but at the end of the session, all of their heart rates were normal (100-170 beats per minute) and stable. Practical implications Though KMC has been proven to be an efficient and feasible approach of caring for LBW infants in a hospital setting, there is a lack of evidence on its outcomes in Pakistan. In light of this, we set out to examine the impact of 3 hours of KMC on vital signs in LBW infants, namely their core temperature, heart rate, respiratory rate, and oxygen saturation. The ultimate goal is to collect enough evidence to advocate for the strategy’s widespread adoption. Conclusion: Better quality and more humanized care for preterm and low birth weight babies and their mothers may be achieved by encouraging the use of the Kangaroo Mother Care approach in neonatal intensive care units in Pakistan. Keyword: KMC, temperature, oxygen saturation, respiratory rate, heart rate. Low birth weight